CONGESTION PRICING IN SELECTED CITIES IN SOUTHEAST ASIA - Tan Eng Hwa; Meenchee Hong; Ei Yet Chu (Journal of Islamic, Social, Economics and Development, 2022)
The aim the conceptual paper is to improve the level of the road traffic congestionin selected cities of Southeast Asia through implementation of congestion pricing. Trafficcongestion is a common phenomenon in most cities in Southeast Asia. It is a significantimpediment to the achievement of economic goals. Many remedies have been put forward toease road congestion, some of which is congestion price. Economists and transportationexperts’ views congestion pricing as the most efficient means to mitigate traffic congestionbecause it employs price mechanism. Many research deals with congestion price, and whatamount to be imposed. However, results from these previous studies were not enough to validatewhat should be the components of a congestion price that will regulate and efficiently allocatethe resources. Thus, this conceptual paper suggests to estimate and determine the congestionpricing to be imposed in the selected cities in Southeast Asia based on the value of time oftravellers. It also proposes to further evaluates the effect of congestion pricing on transportinfrastructure investment on the road and in railway. The outcome of the study may act asguidelines for government agencies and transportation authority in developing policies andstrategies to enhance the efficiency of public infrastructure and reduce traffic congestion.